Low coercivity iron-silicon material, shields, and process - TAN; SWIE-IN; VALSTYN; ERICH PHILIPP; AINSLIE; NORMAN GEORGE; HEMPSTEAD; ROBERT DOUGLAS (1977)
Iron-silicon is sputtered onto a substrate to be used for a magnetic recording head from a target containing 4% to 7% of silicon with a substrate bias between -2.5 and -60 volts, anode-cathode spacing of about 1/2 to about 2 inches, a deposition rate of greater than 150A/min, a substrate temperature above 250 DEG C, an argon pressure above 10 microns, and a single film thickness greater than 0.4 micron, a laminated film thickness greater than 0.05 micron, and R.F. input power above 8 watts/in2.